Burnout and moral injuries after foreign deployment among medical personnel of the German armed forces: a pre-post study - Langner, Franziska; Börke, Anna Katharina; Muschner, Patric; Muther, Maria; Reichelt, Andreas; Willmund, Gerd-Dieter; Wesemann, Ulrich; Zimmermann, Peter Lutz; Schönsee, Isabel (Frontiers in Psychiatry, 2024)
Introduction Given a high amount of workplace stressors, burnout syndrome, as a depression-related syndrome, is highly relevant for medical service soldiers. This study aims to examine their effects with regard to moral injuries and personal values following foreign deployment. Materials and methods This longitudinal study included 91 soldiers of the German Armed Forces Medical Service. Participants completed the Maslach Burnout Inventory (MBI) and the Portrait-Value-Questionnaire (PVQ) before and after a foreign deployment as well as the Moral Injury Scale (SMBE) after deployment. Analysis has been conducted using t-tests to assess potential changes in MBI and PVQ scales between pre-test - t1 (2-4 weeks before deployment) and post-test – t2 (up to 6 months after deployment). In addition, correlations were examined between moral injuries (MI) after deployment and MBI scores at t1 and t2 as well as between personal values (PVQ t1) and MBI scores at t1 and t2. Results The MBI subscales showed mild to moderate burnout symptoms at both pre- and post-tests, with a slight deterioration during the study period, albeit not significant. There were no significant mean differences in PVQ between measurement points. Nevertheless, PVQ self-direction and tradition at t1 correlated negatively with MBI INV at t2 (PVQ SD r = -.21, p = .043) and MBI PA at t2 (PVQ TR r = -.23, p = .027). Furthermore, the subscale PVQ power at t1 correlated positively with MBI PA at t2 (PVQ PO r = .28, p = .006), meanwhile PVQ universalism at t1 correlated positively with MBI INV at t1 (PVQ UN r = .25, p = .018). Furthermore, positive correlations were found between moral injuries at t2 (SMBE total score, SMBE_Sub1, SMBE_Sub2) and MBI subscales Emotional Exhaustion (EE; r = -.54, p = .001), Depersonalization (DP; r = .38, p = .001), and Involvement (INV; r = .30, p = .004) before and after the deployment period. No correlation was found between MI and MBI subscale Personal Accomplishment (PA). Conclusion The results indicate that medical service soldiers exhibit mild to moderate burnout symptoms even before deployment. Significant associations between moral injuries and burnout were found in 3 out of 4 MBI subscales (EE, DP, INV). There was a significant association with a stronger moral injury and higher burnout levels, persisting both before and after the study period. Furthermore, our results suggest that personal value orientations might be meaningful predictors of burnout. Hence, causal questions regarding general work stress among medical service soldiers should be further explored in more detailed studies. Further research could lay the foundation for future approaches in psychotherapy as well as primary and secondary prevention in this field.